A search for transit timing variations in the HATS-18 planetary system. Issue 3 (12th July 2022) - Southworth, John; Barker, A J; Hinse, T C; Jongen, Y; Dominik, M; Jørgensen, U G; Longa-Peña, P; Sajadian, S; Snodgrass, C; Tregloan-Reed, J; Bach-Møller, N; Bonavita, M; et al.
ABSTRACT: HATS-18 b is a transiting planet with a large mass and a short orbital period, and is one of the best candidates for the detection of orbital decay induced by tidal effects. We present extensive photometry of HATS-18 from which we measure 27 times of mid-transit. Two further transit times were measured from data from the Transiting Exoplanet Survey Satellite ( TESS ) and three more taken from the literature. The transit timings were fitted with linear and quadratic ephemerides and an upper limit on orbital decay was determined. This corresponds to a lower limit on the modified stellar tidal quality factor of $Q_\star ^{\, ′ } \gt 10^{5.11 ± 0.04}$ . This is at the cusp of constraining the presence of enhanced tidal dissipation due to internal gravity waves. We also refine the measured physical properties of the HATS-18 system, place upper limits on the masses of third bodies, and compare the relative performance of TESS and the 1.54 m Danish Telescope in measuring transit times for this system.